Utilization of Project Management tool in Construction Industry : A Review - Singh, Ishan; Gupta, Sandeep; Awasthi, Surbhi (International Journal of Scientific Research in Civil Engineering, 2021)
Attributable to an augmenting context of environment, Construction industry is ever upfront for the development and advancement in tools and equipment features, tools of communication, techniques of efficient management, educating the human resources about it. The acceptance of the software Primavera as a platform of scheduling is been on a boom in Multi National Construction Companies, but due to ignorance and lack of Project Management concepts and discourage towards the use of computer based programs, small and medium scale Indian construction companies confront various issues such as inefficient planning, project delays, inefficiency of resources and many other issues. Therefore, attempt to educate one such medium scale construction company about the advantages of Primavera in execution of any construction projects efficiently. This paper presents literature review of journals related to project management.